PENERAPAN ALGORITMA NEAREST NEIGHBOR DALAM MEMPREDIKSI KELAYAKAN PENERIMAAN KARTU KREDIT PADA BANK CIMB NIAGA - Ndruru, Eferoni; Zebua, Taronisokhi (Universitas Methodist Indonesia, 2019)
A credit card application is a financial facility that allows a person or business entity to borrow money to buy a product and pay it back within a specified time. Credit card manufacture often experiences risk in providing credit, both moderate, good and very good risk, due to lack of data analysis and lack of attention. So the purpose of this study is to analyze the risks that often occur in making credit cards. And provide efficient solutions. In solving this problem, it is necessary to apply the method. The method used in this study is Nearest Neighbor. The Nearest Neighbor algorithm is an approach to finding cases by calculating the proximity between new cases (testing data) and old cases (training data), which is based on matching the weights of a number of existing features. Therefore, it can be applied in analyzing old customer data with data new so that comparisons can be made whether or not it is eligible to receive credit. The results obtained in this study are the results of testing systems and methods by producing a level of risk.